Displaying curves, surfaces and solid objects in unity 3D system - Beh, Wei Feng (Nanyang Technological University, 2022)
Computer Graphics and Visualization (CZ2003) is a course in Nanyang Technological University designed to introduce methods for visualising data. The course made use of a visualization tool FVRML, which is a function-based extension of Virtual Reality Modelling Language to allow for time-dependent shape modelling on the Web. FVRML allowed students to visualize shapes by providing mathematical equations of objects. However, due to dependency issues of BS Contact – a 3D player plug-in for Microsoft Internet Explorer – which FVRML relied on, a new application, Shape Explorer was developed. Shape Explorer was developed by another student, Khiew Jian Bin, using the Unity3D platform. Subsequently, a few other students have worked on the project to improve its usability and stability. The latest stable version developed by Khan Naseer Ahmed served its purpose of allowing students to visualize objects well, but still has room for improvements, such as added functionalities. This study was aimed to propose new functionalities that will allow better teaching of the CZ2003 course it was designed to serve, by overcoming previously implemented limitations to recreate a more complete user-experience.